2019
DOI: 10.1200/jco.2019.37.15_suppl.5518
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled phase II trial comparing gemcitabine monotherapy to gemcitabine in combination with adavosertib in women with recurrent, platinum resistant epithelial ovarian cancer: A trial of the Princess Margaret, California, Chicago and Mayo Phase II Consortia.

Abstract: 5518 Background: Platinum resistant ovarian cancer (OC) remains a therapeutic challenge. High grade serous OC (HGSOC) harbors TP53 mutations leading to increased dependency on S- and G2-phase checkpoints. Wee1 inhibition with Adavosertib (AZD 1775) (A) induces G2 checkpoint escape. Gemcitabine (G) is an antimetabolite therapy and blocks the progression of cells through the G1/S phase. We hypothesized that combining G+A would be synergistic and overcome resistance. Methods: We conducted a multicentre double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A recent randomised phase II study assessed the combination of AZD1775 and gemcitabine, versus gemcitabine monotherapy, in platinum resistant HGSOC [105]. Impressively, a survival benefit was observed, with median Overall Survival 11.5 months with combination treatment, compared to 7.2 months in the gemcitabine arm (Hazard Ratio 0.56, 95% Confidence Interval 0.34-0.92; p = 0.022).…”
Section: Cell Cycle Checkpoint Inhibitorsmentioning
confidence: 99%
“…A recent randomised phase II study assessed the combination of AZD1775 and gemcitabine, versus gemcitabine monotherapy, in platinum resistant HGSOC [105]. Impressively, a survival benefit was observed, with median Overall Survival 11.5 months with combination treatment, compared to 7.2 months in the gemcitabine arm (Hazard Ratio 0.56, 95% Confidence Interval 0.34-0.92; p = 0.022).…”
Section: Cell Cycle Checkpoint Inhibitorsmentioning
confidence: 99%
“…Preliminary results from an open-label, four-arm, Phase II study of adavosertib plus four different types of chemotherapy regimens in patients with platinum-resistant ovarian cancer also suggested that adavosertib plus carboplatin shows promise in terms of efficacy [16]. Furthermore, a randomized Phase II study, also in women with platinumresistant ovarian cancer, has demonstrated that adavosertib and gemcitabine combination therapy improves treatment efficacy compared with gemcitabine alone [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was also a statistically significant improvement in overall survival (OS) from 7.2 to 11.5 months (HR 0.56 (95% CI 0.34-0.92, P=0.022) and increased number of patients with PR from 3 to 21% (p=0.02). Again, there was increased grade 3/4 AEs especially hematological toxicity including anemia (31 vs 18%), thrombocytopenia (31 vs 6%), and neutropenia (62 vs 30%) in adavosertib arm compared to placebo arm, respectively [13]. Most of the preclinical and clinical studies have been performed using WEE1 inhibitor from AstraZeneca, namely AZD1775 (MK1775 or adavosertib).…”
Section: Clinical Trials Of Adavosertib Monotherapy and In Combination With Different Chemotherapiesmentioning
confidence: 99%
“…A double-blind randomized phase 2 trial showed that addition of adavosertib (175mg od on D1–2, D8–9, and D15–16) to gemcitabine (1000mg/m 2 IV D1, D8, and D15 in a 28-day cycle) (Table 1 ) improved PFS from 3.0 to 4.6 months (HR 0.56 (95% CI 0.35–0.90, p=0.015 Log rank) compared to placebo arm in patients with recurrent platinum-resistant/refractory high-grade serous ovarian cancer (HGSOC) [ 13 ](NCT02151292). In addition, there was also a statistically significant improvement in overall survival (OS) from 7.2 to 11.5 months (HR 0.56 (95% CI 0.34–0.92, P=0.022) and increased number of patients with PR from 3 to 21% (p=0.02).…”
Section: Clinical Trials Of Adavosertib Monotherapy and In Combination With Different Chemotherapiesmentioning
confidence: 99%